Base‐promoted Synthesis of Trifluoromethylated (1, 3‐dioxolan‐4‐ylidene)methylphosphonates from Trifluoromethylketones and Ethynylphosphonates. Issue 10 (12th September 2021) - Mitrofanov, Alexander Yu.; Nefedov, Sergey E.; Beletskaya, Irina P.
Abstract: Efficient synthesis of CF3 ‐functionalized 1, 3‐dioxolane phosphonates via base‐catalyzed nucleophilic addition/cyclization of diethyl ethynylphosphonate or diethyl 3‐hydroxyprop‐1‐yn‐1‐ylphosphonates with trifluoromethylketones is described. Synthesis of various CF3 ‐substituted 1, 3‐dioxolane derivatives in good to excellent yields with a broad range of substrates is described. Abstract : Convenient approach to a series of CF3 ‐functionalized (1, 3‐dioxolan‐4‐ylidene)methylphosphonates using trifluoromethylketones and different alkynylphosphonate was developed. In the case of diethyl ethynylphosphonates reaction smoothly proceed at room temperature in the presence of KO‐ t Bu giving 2, 5‐bistrifluoromethylated 1, 3‐dioxolanes derivatives in high yields. Diethyl (3‐hydroxyprop‐1‐yn‐1‐yl)phosphonates resulted 2‐CF3 ‐fuctionalized derivatives in good yields.